2014
DOI: 10.3892/ijo.2014.2247
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the Kank1 gene-induced brain glioma apoptosis and blockade of the cell cycle in G0/G1 phase

Abstract: The Kank1 gene is one of the important members of the Kank gene family. As an important adaptor protein, Kank1 plays a significant role in the genesis and development of many malignant tumors. It was recently discovered that the Kank1 gene is a new cancer suppressor, and its expression is significantly downregulated or it is not expressed in kidney cancer, bladder cancer, prostate cancer, lung cancer and breast cancer. However, no report on the role of Kank1 in the genesis of brain glioma is available to date.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Similarly, a recent study with glioma cell lines confirmed that KANK1 transient re-expression was able to block cells in the G 1 /G 0 phase32. Although cell growth suppression is consistent with previous reports, G 1 /G 0 cell cycle arrest was not seen in our doxycycline-inducible stable MPNST cells.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, a recent study with glioma cell lines confirmed that KANK1 transient re-expression was able to block cells in the G 1 /G 0 phase32. Although cell growth suppression is consistent with previous reports, G 1 /G 0 cell cycle arrest was not seen in our doxycycline-inducible stable MPNST cells.…”
Section: Discussionsupporting
confidence: 93%
“…High grade glioma is the leading cause of brain cancer-related mortality due to its high invasive ability and malignant proliferation (1,2). Glioma incidence accounts for approximately 40-50% of all intracranial tumors (3).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we detected Bcl ¡ 2 and its related BAX, Caspase-9 and Caspase-3 expression, 20 and found that Bcl ¡ 2 levels increased, whereas BAX levels decreased in irradiationinduced A549/34R cells compared with those in A549 controls (Fig. 3C).…”
Section: 19mentioning
confidence: 99%